Surface Modification of Polycaprolactone Scaffold With Improved Biocompatibility and Controlled Growth Factor Release for Enhanced Stem Cell Differentiation - Qin, Xiaoyan; Wu, Yixin; Liu, Shuang; Yang, Lei; Yuan, Hongxia; Cai, Susu; Flesch, Julia; Li, Zehao; Tang, Yujing; Li, Xiaomin; Zhuang, Yi; You, Changjiang; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
Polycaprolactone (PCL) has been widely used as a scaffold material in the tissue engineering field. However, its great potentials have been limited by their hydrophobic characteristics and lack of bioactive molecules to modulate cell growth. Here, we report a surface modification strategy for hydrophobic PCL scaffold using an azide-terminated amphiphilic polymer, which can be further functionalized with dibenzocyclooctyne (DBCO)-modified growth factor nanocapsules through the azide-alkyne ‘click chemistry’. With multivalent alkylation and pegylation on the side chains, stable coating of the graft polymer on the PCL scaffold was achieved in one step, which provides the scaffold with better cell adhesion and growth. In addition, through specific immobilizing of pH-responsive BMP-2 nanocapsules onto the modified PCL scaffold, controlled release of active BMP-2 was achieved within 21 days. When bone mesenchyme stem cells were cultured on the modified scaffold, enhanced ossification was observed in correlation with the time-dependent release of BMP-2. The enhanced stem cell differentiation established on the n(BMP)-modified scaffold can be extended as a general approach for bioactive functionalization of other hydrophobic scaffold materials with other therapeutic proteins in a variety of clinical applications.